Lessons of the Great Recession for the global economy and CEE countries - Szydło, Wiktor (Lekcje Wielkiej Recesji dla gospodarki światowej i krajów Europy Środkowo-Wschodniej, 2011)
The scope and severity of recent financial crisis (dubbed “Great Recession”) could only be compared with the Great Depression of the 1930s. Yet, it is still not obvious whether recent financial and economic turmoil will prompt the same breakthrough in the discipline (triumph of Keynesian economics) and practice (New Deal). Before an implementation of any sensible reform one needs to learn the origins of the crisis. As they are most likely structural (inadequate institutions and growing income inequality, etc.), the article argues that there is a need for a paradigm shift in development theory and practice
Ekonomia = Economics, 2011, Nr 2 (14), s. 58-67
Keywords: Great Recession; financial crisis; global imbalances; neoliberalism